Tongue Cancer Cell-Derived CCL20 Induced by Interaction With Macrophages Promotes CD163 Expression on Macrophages - Shigeoka, Manabu; Koma, Yu-ichiro; Kodama, Takayuki; Nishio, Mari; Akashi, Masaya; Yokozaki, Hiroshi (Frontiers in Oncology, 2021)
Background: CD163-positive macrophages contribute to the aggressiveness of oral squamous cell carcinoma. We showed in a previous report that CD163-positive macrophages infiltrated not only to the cancer nest but also to its surrounding epithelium, depending on the presence of stromal invasion in tongue carcinogenesis. However, the role of intraepithelial macrophages in tongue carcinogenesis remains unclear. In this study, we assessed the biological behavior of intraepithelial macrophages on their interaction with cancer cells. Materials and Methods: We established the indirect coculture system (intraepithelial neoplasia model) and direct coculture system (invasive cancer model) of CD163-positive macrophages with SCC25, a tongue squamous cell carcinoma (TSCC) cell line. Conditioned media (CM) harvested from these systems were analyzed using cytokine array and enzyme-linked immunosorbent assay and extracted a specific upregulated cytokine in CM from the direct coculture system (direct CM). The correlation of both this cytokine and its receptor with various clinicopathological factors were evaluated based on immunohistochemistry using clinical samples from 59 patients with TSCC. Moreover, the effect of this cytokine in direct CM on the phenotypic alterations of human monocytic leukemia cell line THP-1 was confirmed by real-time polymerase chain reaction, western blotting, immunofluorescence, and transwell migration assay. Results: It was shown that CCL20 was induced in the direct CM specifically. Interestingly, CCL20 was produced primarily in SCC25. The expression level of CCR6, which is a sole receptor of CCL20, was higher than the expression level of SCC25. Our immunohistochemical investigation showed that CCL20 and CCR6 expression was associated with lymphatic vessel invasion and the number of CD163-positive macrophages. Recombinant human CCL20 induced the CD163 expression and promoted migration of THP-1. We also confirmed that a neutralizing anti-CCL20 antibody blocked the induction of CD163 expression by direct CM in THP-1. Moreover, ERK1/2 phosphorylation was associated with the CCL20-driven induction of CD163 expression in THP-1. Conclusions: Tongue cancer cell-derived CCL20 that was induced by interaction with macrophages promotes CD163 expression on macrophages